STUDI PUSTAKA TENTANG INTEGRASI TEKNOLOGI INFORMASI DALAM PEMBELAJARAN AKUNTANSI - Suryanto, Edy; Mukhibun , Akhmad; Laily , Inayah Iffatul; Ridlo , Muhamad Fais Nur; Rahayu , Imta Putri (Cendikia: Jurnal Pendidikan dan Pengajaran, 2025)
This study aims to examine the integration of information technology in the accounting learning process through a qualitative descriptive approach using a literature review method. Data were collected from various credible scientific sources, such as academic journals and research reports obtained through databases like Google Scholar, Sinta, and ScienceDirect. The results of the review indicate that the application of information technology, including accounting software, interactive media, and digital learning platforms, contributes significantly to improving the effectiveness, efficiency, and student engagement in the learning process. Furthermore, technology helps prepare students to face the increasingly digitalized demands of the job market. However, several obstacles are still encountered, including limited infrastructure, low digital literacy among students, and insufficient technological skills among educators. To address these challenges, an integrated strategy is required, including continuous training, improved access to digital facilities, strengthened digital literacy, and curriculum adjustments to align with technological developments. Through this approach, it is expected that accounting education can develop adaptively, remain relevant, and be competitive in the digital era and the Fourth Industrial Revolution.